2021
DOI: 10.1371/journal.pone.0256493
|View full text |Cite
|
Sign up to set email alerts
|

Peoples’ understanding, acceptance, and perceived challenges of vaccination against COVID-19: A cross-sectional study in Bangladesh

Abstract: In order to eliminate COVID-19, many countries provided vaccinations. However, success depends on peoples’ knowledge levels and rates of acceptance. But, previous research on this topic is currently lacking in Bangladesh. This cross-sectional study aimed at to investigate Bangladeshi peoples’ knowledge, acceptance, and perception of challenges regarding COVID-19 vaccines. Quantitative data were collected using an online survey (n = 1975) and face-to-face interviews (n = 2200) with a pre-tested structured quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 33 publications
3
21
0
1
Order By: Relevance
“…Additionally, three studies were conducted in each Malaysia ( 43 45 ) and Kuwait ( 27 , 46 ). Two studies conducted in each Qatar ( 47 , 48 ), Italy ( 15 , 49 ), Jordan ( 27 , 50 ), Bangladesh ( 51 , 52 ), Ethiopia ( 53 , 54 ), Taiwan ( 55 , 56 ), and Germany ( 57 , 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, three studies were conducted in each Malaysia ( 43 45 ) and Kuwait ( 27 , 46 ). Two studies conducted in each Qatar ( 47 , 48 ), Italy ( 15 , 49 ), Jordan ( 27 , 50 ), Bangladesh ( 51 , 52 ), Ethiopia ( 53 , 54 ), Taiwan ( 55 , 56 ), and Germany ( 57 , 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our study found that only academic information is the predictor of knowledge, attitude, and hesitancy towards the COVID-19 vaccine. Several studies on COVID-19 vaccine hesitancy among Bangladeshi respondents evaluated socio-demographic information, behavioral predictors, and academic information [ 18 20 ]. One study conducted among Czech university students found socio-demographic information such as gender and nationality as significant predictors of COVID-19 vaccine hesitancy [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study is necessary to determine these students’ knowledge, attitude, and hesitancy (KAH) concerning COVID-19 vaccinations. Apart from the significance of this study, there was a dearth of research on university students, with the exception of a few studies on the general population of Bangladesh [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Penyakit ini dikenal dengan Covid-19 yang ditemukan pada tahun 2019 dan belum pernah menyerang manusia sebelumnya. World Health Organization (WHO) mengumumkan kedaruratan internasional pada 30 Januari 2020, dengan pernyataan sebagai 'pandemi' pada 11 [12][13][14][15][16][17][18] Penelitian Wahyuni, dkk (2021) menyatakan bahwa terdapat lima faktor penerimaan vaksinasi yaitu akses, keterjangkauan, kesadaran, penerimaan, dan aktivasi. faktor yang pengaruhnya paling besar adalah faktor kesadaran, keterjangkauan, dan penerimaan, sedangkan faktor yang kurang berpengaruh adalah faktor aktivasi dan akses.…”
Section: Pendahuluanunclassified